Sleep ecology, sleep characteristics and behavior problems in young maltreated children: A scoping review. (December 2021) - Servot, Sabrina; St-Amand, Annick; Rousseau, Michel; Simard, Valérie; Touchette, Evelyne
Abstract: Background: Behavior problems are highly prevalent in young maltreated children. Their etiology is multifactorial and has been widely documented. Lately, researchers paid increased attention to the role of sleep in non-maltreated children's behavior problems. They showed that poor sleep (e.g., short sleep duration, nocturnal awakenings) increased behavior problems. In addition, an inadequate sleep ecology (e.g., lack of sleep hygiene or bedtime routine) may lead to sleep problems. Objective: As maltreated children often live in disorganized environments, this study aims to map knowledge about sleep ecology and sleep characteristics, as well as their associations with behavior problems in young maltreated children from one to five years old. Method: A scoping review was performed according to the PRISMA-SR checklist. Bibliographic databases were searched from 1993 to May 2020. Results: From the 650 studies screened, nine reported results about sleep ecology or sleep characteristics or their associations with behavior problems in young maltreated children. Only one study described their sleep ecology. Eight studies documented or compared sleep characteristics, showing slight differences between maltreated and non-maltreated children (e.g., longer nighttime sleep duration or shorter naps in maltreated children). Four studies revealed associations between sleep characteristics and behavior problems in young maltreated children (e.g., shorter sleep duration was associated with more externalizing behaviors). Conclusion: Literature about sleep ecology, sleep characteristics, as well as with their associations with behavior problems in young maltreated children is scarce. Their sleep ecology especially deserves to be investigated. Longitudinal studies, studies with comparison groups, combining objective and subjective validated sleep measures, and taking into account maltreatment characteristics and children's developmental stage should be pursued.